Allergic subjects express intercellular adhesion molecule — 1 (ICAMA or CD54) on epithelial cells of conjunctiva after allergen challenge - Ciprandi, Giorgio; Buscaglia, Sandra; Pesce, Giampaola; Villaggio, Barbara; Bagnasco, Marcello; Canonica, Giorgio Walter (Journal of allergy and clinical immunology, 1993)
Background: Allergic inflammation can be experimentally reproduced in vivo in humans, by means of the conjunctival provocation test with allergen. The allergen stimulation triggers an early clinical response and an almost simultaneous cellular infiltrate. Among the factors that can contribute to the local cellular recruitment, we postulate a possible early involvement of CD54 in the development of inflammation caused by the allergic reaction. Methods: We used a sensitive immunocytochemical immunoenzymatic alkaline phosphatase-monoclonal antialkaline phosphatase technique to detect the possible expression of CD54 molecule on epithelial cells of conjunctiva in 15 allergic subjects and in 15 healthy individuals in basal conditions and after allergen challenge ( Parietaria judaica) during the off-pollen season. Results: At baseline all studied individuals did not evidence CD54 expression on epithelial cells; 30 minutes after allergen challenge, all the allergic individuals showed a marked expression of CD54 on conjunctival epithelium, whereas none of healthy subjects showed any CD54 expression. First, CD54 expression on conjunctival epithelium after specific provocation test appeared as a specific phenomenon occurring only in sensitized subjects; moreover, it is an immediate event concomitant with the local inflammatory infiltrate. Therefore conjunctival epithelium unexpectedly appeared to be more than a bystander in the allergic reaction; it may be perceived as an active participant interacting with the inflammatory infiltrate. Conclusions: These findings indicate that CD54 may play a central role in the allergic inflammation and strongly support the concept that maneuvers designed to interact with the adhesion machinery expressed on inflammatory cells and epithelium may be a helpful therapeutic approach.